Hellenic model of education and its axioms in modern sport - Kaźmierczak, Arkadiusz (Journal of Education, Health and Sport, 2018)
Ancient Greece of modern civilization has left an extremely valuable heritage in the form of sports games. The ideals of ancient Hellas - a cornerstone of European culture - accompanied the great games organized for many centuries in Olympia. Contemporary sport originating from the Greek ancient culture in its axiological aspirations constantly refers to Kalos kagathos, which is an ideal combining truth, good and beauty. The inspiring starting point for the founder of the Olympic movement was the ancient Greek philosophy, which the educator and reformer of the education and school system wanted to include in the European education system. However, the basic elements on which the French aristocrat built the ideology of Olympism were the ideas and intellectual currents of the age of enlightenment, such as: equality, progress, individuality, respect and understanding of cultural diversity, freedom and tolerance of human behavior.